Sequential delivery of antibiotics and probiotics employing a dual release mechanism - Govender, Mershen (My University, 2015)
Antibiotic therapy has been proven to be vital for the treatment of life-threatening bacterial infections. Oral antibiotic therapy, however, results in unwanted side effects such as the intestinal flora destruction, allowing for the colonization of foreign bacteria. This phenomenon results in the occurrence of antibioticassociated diarrhea. Probiotic supplementation has been the choice adjunctive prophylaxis for this condition allowing for the bacterial adhesion of intestinal mucosal binding sites. Probiotic bacteria are, however, susceptible to the bactericidal effects of broad-spectrum antibiotics, resulting in many probiotic formulations being prescribed two hours after the ingestion of the antibiotic formulation. This is, however, not always adhered to, with many patients taking the antibiotic and probiotic concomitantly resulting in the destruction of the probiotic bacteria. This study provides for the design, development, characterization and evaluation of an oral delivery system for the concurrent administration of antibiotics and probiotics employing a dual release mechanism or ‘Dual-Biotic System’. The premise behind the development of this system is to allow for the concurrent administration of antibiotics and probiotics where the probiotic bacteria are only released two hours after the antibiotic, in which time the antibiotic would be absorbed into systemic circulation, preventing physical interaction between the systems and thus preventing bacterial destruction. Amoxicillin was chosen as the model antibiotic in this study due to its spectrum of activity and wide utilization in oral antibiotic therapy.
Keywords: Drug Delivery Systems; Delayed-Action Preparations